Assessment of the induced effect of selected iron hydroxysulfates biosynthesized using Acidithiobacillus ferrooxidans for biomineralization of acid mine drainage. (4th April 2023) - Wang, Heru; Guo, Qian; Guo, Zehao; Luo, Haowei; Li, Honghu; Yang, Jun; Song, Yongwei
Abstract: Soluble iron and sulfate in acid mine drainage (AMD) can be greatly removed through the formation of minerals facilitated by seed crystals. However, the difference in the effects of jarosite and schwertmannite as endogenous seed crystals to induce AMD mineralization remains unclear. This paper intends to study the effect of Fe 2+ oxidation and Fe 3+ mineralization in the biosynthesis of minerals using different addition amounts and methods of jarosite or schwertmannite. The results showed that the addition amount and method of different seed crystals had no effect on the Fe 2+ bio-oxidation but would change the Fe 3+ mineralization efficiency. With the same amount of seed crystals added, jarosite exhibited a higher capacity to promote Fe 3+ mineralization than schwertmannite. Adding seed crystals before the initiation of Fe 2+ oxidation (0 h) could significantly promote Fe 3+ mineralization efficiency. With the increase of seed crystals, jarosite could not only shorten the time required for mineral synthesis but also improve the final mineral yield, whereas schwertmannite could only shorten the time required for mineral synthesis. When Fe 2+ was completely oxidized to Fe 3+ (48 h), the supplementary of jarosite could still effectively improve Fe 3+ mineralization efficiency, but the addition of schwertmannite no longer affected the final mineralization degree. HIGHLIGHTS: The addition of jarosite and schwertmannite had no significant effect on the bio-oxidation of Fe 2+ by A. ferrooxidans but would change the mineralization efficiency of Fe 3+ . The effect of jarosite addition on the mineralization of Fe 3+ was much greater than that of schwertmannite addition. Adding seed crystals before the initiation of Fe 2+ oxidation could significantly promote Fe 3+ mineralization efficiency. Graphical Abstract